The Topic of “Sin” in Judges 10:6-16 - Kalev, Zoran (Forum Theologicum Sardicense, 2025)
Zoran Kalev (Assist. Professor of Old Testament at the University of Sofia) The Topic of “Sin” in Judges 10:6-16 The textual unit in Judges 10:6-16 is a dramatic testimony featuring a dialogue between God and the entire nation of Israel. The aim of this article is to focus on the structure of this text from the Book of Judges. The method of analysis employed is source criticism. The examination includes various hypothetical explanations addressing the following questions: Is there an older literary tradition incorporated in Judges 10:6-16? Furthermore, does the speech of God suggest a specific Old Testament genre addressing the sin of idolatry?